Enamel Remineralisation and Antimicrobial Efficacy of a Withania somnifera, Ficus religiosa, Salvia rosmarinus-based Polyherbal Gel: A Research Protocol - Rijuta Gujar; Punit Fulzele; Nilima Thosar; Anjori Raut (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Dental caries is a multifactorial and chronic disease. Streptococcus mutans and Lactobacillus species are the primary microorganisms responsible for dental caries and enamel demineralisation. Caries can be prevented by fluoridated products like Casein Phosphopeptide- Amorphous Calcium Phosphate (CPP-ACP) or non fluoridated products. CPP-ACP can be used as a remineralising agent. Fluoride can also be used only as a remineralising agent. This article focuses on Withania somnifera, Ficus religiosa, and Salvia rosmarinus, which have all the three properties- antibiofilm, antimicrobial and remineralising. Need of the study: Dental caries is a significant oral disease due to bacterial biofilms and enamel demineralisation. Traditional chemical medicaments such as fluoride have drawbacks of toxicity and resistance. Therefore, safer natural substitutes are desired. Withania somnifera, Ficus religiosa, and Salvia rosmarinus have antimicrobial, antioxidant, and remineralising activities. But they have to be studied in combination as a polyherbal gel for enamel. Therefore, the present study aims to assess the antimicrobial, antibiofilm, and remineralisation capability of this plant formulation, providing a biocompatible and effective means to prevent dental caries. Aim: To evaluate the antimicrobial, antibiofilm and remineralisation efficacy of Withania somnifera, Ficus religiosa and Salvia rosmarinus-based polyherbal gel on enamel. Materials and Methods: An in-vitro study will be conducted in the Department of Paediatric and Preventive Dentistry, Datta Meghe Institute of Higher Education and Research, Wardha, Maharashtra, India, from December 2025 to December 2026. In the present study, teeth extracted for orthodontic purposes or teeth samples with non cavitated lesions suitable for remineralisation assessment will be selected. Total teeth will be 70, with two groups each containing 35 teeth, n=35. Group 1: Withania somnifera, Ficus religiosa, Salvia rosmarinus. Group 2: Control group CPP-ACP. Antimicrobial efficacy will be determined against oral pathogens with the agar diffusion and broth microdilution techniques. Antibiofilm activity will be evaluated using biofilm inhibition and disruption assays. The remineralisation ability will be examined by scanning electron microscopy. A paired t-test will be applied to compare biofilm reduction before and after treatment within the same group. An independent t-test will be used to compare outcomes between two independent groups (polyherbal gel and controlCPP-ACP). The p-value of ≤0.05 will be considered statistically significant.